The Effect of Think-Talk-Write Cooperative Learning Assisted by GeoGebra Software on Students' Critical Thinking (Case Study of SMA AL-HIDAYAH Medan) - Ahmad Rahmatika (UMSU, 2022)
This study aimed to see or describe the effect of cooperative learning type think talk write assisted by GeoGebra software on students' critical thinking at SMA Al-Hidayah Medan. In the current learning period, there are still many students who use the memorization learning method, without knowing how the formula process actually works. Certainly, there is no student's ability to think critically to make them understand the formulas given by the teachers. This study used a quantitative approach, with the SPSS analysis tool and the ANOVA test. The results obtained that the group score of the GeoGebra-assisted TTW learning model and the ordinary learning model obtained a value of Fcount = 9.406 Ftable = 3.140 and with sig = 0.003. Because the sig level is less than 0.05, so Ho is rejected and H1 is accepted. So it can be concluded that there is an effect of using the TTW type cooperative learning model with the help of GeoGebra software on students' mathematical critical thinking skills.